Brain and Muscle Metabolic Changes by FDG-PET in Stiff Person Syndrome Spectrum Disorders - Wang, Yujie; Sadaghiani, Mohammad S.; Tian, Fan; Fitzgerald, Kathryn C.; Solnes, Lilja; Newsome, Scott D. (Frontiers in Neurology, 2021)
Objective: To report clinical characteristics and fluorodeoxyglucose positron emission tomography (FDG-PET) findings in the brain and muscles of individuals with stiff person syndrome (SPS) spectrum disorders (SPSSDs). Methods: Retrospective cohort study from 1997 to 2018 at Johns Hopkins Hospital identified 170 individuals with SPS or cerebellar ataxia (CA) associated with anti-glutamic acid decarboxylase (anti-GAD)-65 antibodies. Fifty-one underwent FDG-PET, with 50 involving the body and 30 with dedicated brain acquisition. The clinical and immunological profiles were extracted via medical record review. The brain scans were analyzed quantitatively using the NeuroQ software, with comparison with an averaged normal database. The body scans were reviewed qualitatively by a blinded nuclear medicine radiologist. Results: Mean age of symptom onset was 41.5 years (range 12–75 years). Majority were female (68%) and White (64%). Of the patients, 82% had SPS (majority being classic phenotype), and 18% had CA. Three had a paraneoplastic process. Forty-seven had serum anti-GAD, two with anti-amphiphysin, and one with anti-glycine receptor antibodies. Brain metabolic abnormalities were seen in both SPS and CA, with significant differences between the groups noted in the right superior frontal cortex, right sensorimotor cortex, left inferior parietal cortex, bilateral thalami, vermis, and left cerebellum. Of the patients, 62% demonstrated muscle hypermetabolism, most commonly bilateral, involving the upper extremities or axial muscles. Neither brain nor muscle metabolism was correlated with functional outcomes nor treatments. Conclusions: Metabolic changes as seen by FDG-PET are present in the brain and muscle in many individuals with SPSSD. Future studies are needed to assess whether FDG-PET can help aid in the diagnosis and/or monitoring of individuals with SPSSD.